Analysis of advanced vapor source for cadmium telluride solar cell manufacturing - Khetani, Tejas Harshadkumar, author; Sampath, Walajabad, advisor; Sakurai, Hiroshi, committee member; Sites, James, committee member (Colorado State University. Libraries, 2013)
A thin film CdS/CdTe solar cell manufacturing line has been developed in the Materials Engineering Laboratory at Colorado State University. The original design incorporated infrared lamps for heating the vapor source. This system has been redesigned to improve the energy efficiency of the system, allow co-sublimation and allow longer run time before the sources have to be replenished. The advanced vapor source incorporates conduction heating with heating elements embedded in graphite. The advanced vapor source was modeled by computational fluid dynamics (CFD). From these models, the required maximum operating temperature of the element was determined to be 720 C for the processing of CdS/CdTe solar cells. Nichrome and Kanthal A1 were primarily selected for this application at temperature of 720 °C in vacuum with oxygen partial pressure. Research on oxidation effects and life due to oxidation as well as creep deformation was done, and Nichrome was found more suitable for this application. A study of the life of the Nichrome heating elements in this application was conducted and the estimate of life is approximately 1900 years for repeated on-off application. This is many orders of magnitude higher than the life of infrared heat lamps. Ceramic cement based on aluminum oxide (Resbond 920) is used for bonding the elements to the graphite. Thermodynamic calculations showed that this cement is inert to the heating element. An earlier design of the advanced source encountered failure of the element. The failed element was studies by scanning electron microscopy and the failure was attributed to loss of adhesion between the graphite and the ceramic element. The design has been modified and the advanced vapor source is currently in operation.
Keywords: cadmium telluride solar cell; ceramic resbond 920; computational fluid dynamics (CFD); nichrome NiCr; oxidation; vacuum heating element